Ethics of Human Cloning: A Comparative Study of Western Secular and Islamic Bioethics Perspectives - Islam, Sharmin; Nordin, Rusli Bin; Shamsuddin, Ab Rani; Noor, Hanapi Bin Mohd (Bangladesh Journal of Medical Science, 2012)
The comparative approach regarding the ethics of surrogacy from the Western secular and Islamic bioethical view reveals both commensurable and incommensurable relationship. It is not either straight forward commensurable or straight forward incommensurable. Islamic bioethics is straight-forward in prohibiting reproductive cloning on its own features and also guess social chaos and anarchy. Western secular bioethics has both arguments and counter arguments both for and against this scientific innovation. Both are eager to highlight the welfare of the society as a whole but the approaches are not always the same. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12595 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12